First principle modelling of the fundamental electronics properties of single layer and bilayer graphene nanoflakes materials - Ng, Wei Jiang (2020)
First principle modelling is computational theoretical modelling used in chemistry, physics and material science to studied the nanomaterials electronic properties. Nevertheless, little research studied has been done on the electronic properties of graphene nanoflakes by using first principle modelling. Therefore, the research aims to investigate the electronic properties of single layer graphene nanoflakes with different shapes by using computational quantum physics modelling which is cost-effective and reliable. The lateral size of the graphene nanoflakes is on the nanoscale and small enough for quantum confinement effect to prevail, which ultimately can lead to an intriguing electronic property that can be studied comprehensively using first principle modelling. Generally, different number of carbon atoms with various shapes of nanoflakes will affect the integrated density of state (IDOS), Fermi energy level and total energy of the scheme. The graphene nanoflakes are studied depended on a detailed theoretical understanding of the electron density wave function (the particular are known as first principle or ab initio calculations).The starting point of the framework is to have a model of the basic atomic configuration of the graphene (which has a hexagonal array of carbon atoms).The configuration is then modelled in terms of it’s the electron density by employing the density functional theory (DFT). The computational method applies the first principle method formed on Density Functional Theory (DFT) with the aid of Quantum ESPRESSO are free and open source computer codes package. Generally, DFT equation E = ∑